Big Data and Information Analytic Support for Indonesian Higher Education: During and after Covid-19 Pandemic - Edy SABARA; Halimah HUSAIN; Faisal SYAFAR (Communications of International Proceedings, 2020)
More than 20 years since the Directorate General of Higher Education of the Ministry of National Education of Indonesia has encouraged the use of technology for education, very few universities have made use of online learning. With the influx of the COVID-19 pandemic, suddenly all lecturers across universities are transforming and even the digital revolution. After the issuance of the Minister of Education and Culture Circular on March 9, 2020 to university leaders to conduct learning from home, in a short time many universities switched to online learning modes. The use of online learning platform is increasingly becoming a trend in the world of education. This trend gave birth to a data explosion in Higher Education which became a new innovation for the world of education, namely Big Data. These large amounts of digital data will provide information on what students and academics see and read, student behavior and involvement, their assessment, motivation and preferences, thus providing a large amount of data that can be extracted for the learning experience. Big Data provides an opportunity to educational Institutions to use their Information Technology resources strategically to improve educational quality and guide students to higher rates of completion, and to improve student persistence and outcomes. This proposes work paper aimed at explores the attributes of big data that are relevant to educational institutions, investigates the factors influencing adoption of big data and analytics in learning institutions and seeks to establish the limiting factors hindering use of big data in Institutions of higher learning.